Directing your heart out : essays for authenticity, engagement and care in theatre - Dugdale, Tom (College teacher) (New York : Methuen Drama, 2023)
"A ground-floor guide to the practice and philosophy of directing that is open to all, including newcomers to the field. Through a series of concise and engaging essays, Directing Your Heart Out will inspire the next generation of theatre directors by encouraging them to approach the craft through instinct, compassion and the uninhibited expression of their own voice and vision. Each of the book's essays deals with a core principle of directing, such as strategies for directing text; facilitating productive discussion in rehearsals; absorbing criticism; and maintaining a positive work environment. Taken together, they serve as an effective introduction to the fundamentals of directing, or as provocative supplementary readings alongside traditional directing textbooks. En route, it references: > more than 20 directors and choreographers > major contemporary ensembles such as The Wooster Group, SITI Company and Back to Back Theatre > key terminology, such as objective, action, obstacle, realism and absurdism > over 12 plays, including a close-reading of a scene from The Seagull Encouraging an approach to directing that is grounded in self-empowerment and is set out accessibly, this book opens up directing to the first-time director or student from a range of backgrounds, as well as the seasoned professional, who will benefit from the many revisionary, fresh perspectives"--